Eastern larch beetle (Dendroctonus simplex LeConte) as a potential threat to western (Larix occidentalis Nutt.) and subalpine larches (Larix lyalli Parl.) - Picklo, Rose M.; Eidson, Erika; Steed, Brytten; Aukema, Brian H. (Frontiers in Forests and Global Change, 2024)
Eastern larch beetle Dendroctonus simplex LeConte has been outbreaking for the past two decades in the Great Lakes region of North America, impacting approximately 400,000 hectares of eastern larch Larix laricina (tamarack) forest in Minnesota, United States, alone. Range expansions of some Dendroctonus species driven by climate change have occurred across North America as rising temperatures increase climatically suitable habitats across latitudes and elevations. The range of eastern larch beetle is currently sympatric to that of its host, eastern larch, but the insect could, in theory, eventually access ranges of other species of Larix native to North America. We compared host suitability of two potential novel hosts, western larch (Larix occidentalis Nutt.) and subalpine larch (Larix lyalli Parl.) against the beetle’s native host, eastern larch, using a reproductive success experiment conducted in cut bolts of all three species. We measured fertility, maternal gallery length, and offspring size and lipid content as metrics of reproductive success. We found beetles could reproduce in both novel Larix species, with subalpine larch having high levels of success compared to the beetle’s native host, eastern larch. These findings suggest that subalpine larch may be at risk should a range expansion of eastern larch beetle occur.